Update on exhaled breath condensate analyses in occupational disease. Issue 2 (April 2020) - Maestrelli, Piero; Mason, Paola; Guarnieri, Gabriella
Abstract : Purpose of review: The present work represents an update of the review published in this journal by Corradi et al., regarding the use of exhaled breath condensate (EBC) to investigate occupational lung diseases. Recent findings: The relevant literature was searched in the Medline database, assessed through PubMed using key terms such as 'breath AND condensate AND occupational'. Eleven pertinent publications were retrieved between January 2018 and October 2019. One article only was related to occupational allergy, and the conclusion is that EBC hydrogen peroxide is not an useful marker in laboratory animal allergy. The biomarkers of exposure most often assessed with EBC are metals. However, it is controversial whether this approach has any advantage over the conventional environmental monitoring. The biomarkers of effect studied by the majority of investigations were those related to oxidative stress. They appear consistently elevated upon occupational exposures to various agents, including welding fumes, crystalline silica, nanomaterials and chemicals. Summary: Although EBC represent a suitable tool to sample airway lining fluid in a noninvasive manner, it remains a niche approach to the investigation of occupational diseases. The confounding influence of EBC dilution should be better addressed in the expression of the results.